An assessment of users' needs of the Don Alejandro A. Roces, Sr. Science-Technology High School Library for the purpose of collection development - Robosa, Karlo Martin M.; Aguirre, Vyva Victoria M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
A library's collection is its most important asset. School libraries with an established collection and effective readers' services help reach the schools' objective. In order to make this possible, library services, as well as the library's collection, must be based upon an understanding of the service community and its information needs and wants (Evans, 2000). It is in this light that this study is focused on the users' needs assessment of Don Alejandro A. Roces, Sr. Science-Technology High School Library.
Respondents of the survey consisted of 319 students and 14 teachers. The Head Librarian and Assistant Librarian were interviewed. Two kinds of questionnaires were distributed: one for the students, another for the teachers. The two questionnaires were subdivided into four sections namely, the personal profile; the use of the library; the users' information needs; and the DARSSTHS Library Collection. Although they consisted of the same sections, the questions were not identical.
According to the study, the students go to the library more than once a week to do research for their assignments, find and read required readings, do their homework and read for pleasure. On the other hand, the teachers go to the library for the purpose of finding materials for teaching, find materials to require their students to read, write examinations, and find teaching techniques. They go to the library for their personal information needs. The students are frequently required to go to the library to do research on their Science, English, and Araling Panlipunan subjects. However, the students find the collection of the library lacking in this kind of materials. Others go to the library to research in the Internet to get more updated information. This study shows that the DARSSTHS library collection does not really serve the curricular and the perceived needs of its clients. The library does not have enough reference materials to fulfill the curricular needs of the students. Also, the library does not have non-book materials like maps and globes that are essential for their Araling Panlipunan subjects. Therefore, this study formulated a Collection Development Policy to help the decision-making for the acquisition of the materials and necessary equipment for the library.
For purposes of improving the collection, the following recommendations must be considered; (1) Seek the support of the school administration for a regular budget in order to cope with the information needs of their clients; (2) Acquire an up-to-date collection of new books, reference materials, and non-book materials such as globe and maps, newspapers and magazines; (3) Implement the proposed Collection Development Policy to ensure that the materials in the library will fulfill the information needs of its clients; (4) Establish a Cataloging System and provide a card catalog to ensure easier retrieval of the materials needed by the clients; (5) Provide library cards to the clients for the security of the materials; and (6) Periodically review and update the Collection Development Policy that will be adopted to cope with the fast changing information needs and demands of the users of the library.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Don Alejandro A. Roces Sr. Science-Technology High School; School libraries -- Collection development -- Philippines -- Quezon City; Library use studies -- Philippines -- Quezon City